The Implications of Board Independence and Foreign Ownership on Audit Quality of Manufacturing Firms in Nigeria - Solomon Oriakhi; Emma .I. Okoye; Segun Idowu Adeniyi (Universitas Airlangga, 2021)
This study investigated the implications of board independence and foreign ownership on audit quality of manufacturing firms in Nigeria. The specific objectives of the study are to examine the effects of board independence as well as foreign ownership on audit quality of manufacturing firms quoted in Nigeria. Secondary data were carefully collected from a total of fifty eight (58) quoted manufacturing firms in Nigeria for the period (2010 – 2018) and the binary model of regression (logit, probit and gombit) was properly used for hypotheses testing. The outcome reveals that board independence had a positive and insignificant influence on audit quality while foreign ownership had a positive and significant influence on audit quality. The study therefore recommends that composition of the board should be such that its function is not undermined and one of such ways is to have an appropriate mixture with non-executive directors. Also having foreign ownership could enhance audit quality given the different corporate cultures they may possess.